Transmission Scheduling Method for Delivery of Large-Sized Data Object Based on Delay Constrained Request over Scheduled Transportation Vehicles - Shigeru Kashihara (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2018)
The paper proposes two transmission scheduling methods to deliver large-sized data object based on delay constrained request over scheduled transportation vehicles. Scheduled transportation vehicles like buses and rails have the potential to provide data communication for delay-tolerant large data object based on delay-/disruption-tolerant network (DTN) concept as a part of the Internet. However, since the operation of vehicles follows the timetable, even if the vehicles carry users' data objects, they may not always deliver the objects to their destination within their requested delay. As one of the approaches, to satisfy the delivery with delay requests, our previous paper presented the design of data offloading to public transportation vehicles. In the model, if a data port accepts data objects from users in a first-come, first-served (FCFS) schedule, the system cannot guarantee to deliver data objects within requested delay. In this paper, as the first step under the design, we propose two transmission scheduling methods for uploading data at a data port. Simulation evaluations demonstrate that the proposed methods significantly improve the successful data delivery compared with FCFS.